Pembuatan dan Karakterisasi Membran Komposit sPEEK-PVA dengan Bahan Isian Grafena Oksida untuk Sel Bahan Bakar Methanol - Elisa Putri Nastiti; Nur Hidayati (Eksergi, 2020)
Direct Methanol Fuel Cell (DMFC) is a fuel cell technology that convert chemical energy into electrical energy directly. Sulfonated polyether ether ketones (sPEEK) have potential as proton exchange membranes. Modification of sPEEK with poly vinyl alcohol (PVA) and adding graphene oxide (GO) is expected to reduce methanol cross over. This study was designed to examine the characteristics of the sPEEK-PVA composite membrane using the independent variable variation of GO 2.5-10% w/w. The results showed that water uptake in the range of 20-33%, swelling degree in the range of 10-17.5%, the ion exchange capacity was 0.59-0.75 meq/g, and the methanol permeability was 2.82-4.2 x10-6 cm2 /s. The characters shown are comparable with Nafion's characters and have the potential to be developed because they are superior in terms of raw material prices